Основні принципи організації викладання дисциплін за вибором - Щука Галина; Shchuka Halyna; Scsuka Halina (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Резюме. Реалізація особистісно-орієнтованого навчання гарантує студентам право самостійно будувати свою освітню траєкторію, обираючи 25 % обсягу освітньої програми. Ряд нормативно-правових актів регулюють організацію даного процесу, але проблемні питання залишаються, що негативно позначається як на якості освітнього процесу, так і на результатах акредитації Освітньо-професійної програми. Для того, щоб цей процес був успішним, необхідно дотримуватися ряду принципів, серед яких: вибіркова дисципліна повинна відповідати потребам здобувача та / або ринку праці; формувати прикладні навики чи загальні компетентності, мати відповідне кадрове, навчально-методичне та матеріально-технічне забезпечення та ін. Спеціалізація забезпечується вивченням кількох дисциплін, які доцільно поєднувати в блоки з чотирьох компонентів (по принципу системи «major»). Таких блоків має бути кілька і вивчаються вони протягом 2 років. Вибіркові дисципліни, які не забезпечують отримання спеціалізації, можуть вивчатися поодинці (по принципу системи «manor») і не мати професійної спрямованості та належати до інших галузей. Змінюється також і роль викладача: від перетворюється на фасилітатора, консультанта, який забезпечує супровід здобувача.

Abstract. The implementation of personal-oriented training guarantees students the right to build their educational trajectory independently, choosing 25% of the educational program volume. A number of normative legal acts regulate the organization of this process, but problematic issues remain, that negatively affects both the quality of the educational process and the results of the accreditation of the Educational and Professional Program. It was established, that in order to make this process successful, a number of principles are to be followed, among which are the following: the optional discipline must meet the needs of the applicant and/or the labour market; form applied skills or general competences, have appropriate personnel, educational and methodological, material and technical support, etc. It was determined that specialization is provided by the study of several disciplines, which should be combined into blocks of four components (according to the principle of the "major" system). There should be several such blocks and they should be studied for 2 years. The optional disciplines, that do not provide specialization, may be studied alone (according to the "minor" system) and may not have a professional orientation and belong to other branches. It is noted that during the teaching of optional subjects, the role of the teacher also changes: he/she turns into a facilitator, a consultant who provides support to the student.
Basic principles of optional subjects teaching organization
Keywords: вибіркові дисципліни; освітній процес; вища освіта